Per l'edizione delle Elegantie di Lorenzo Valla Studio sul V libro - Marsico, Clementina (Premio Ricerca «Città di Firenze», 2013)
Elegantie lingue latine is the masterpiece of Lorenzo Valla's reflection on language, through which the humanist gave birth to a real re-foundation of Latin. To date we still do not have a modern, scientifically based edition of the text characterising the various editorial phases of the work, on which the author worked for over ten years and which, arbitrarily and by the author's own will, was in circulation long before its official publication. This research is part of a future complete edition of the text: the first complete edition of a book of the "Elegantie" is presented, limited to the fifth book on the "disputatio verborum", based on the examination, albeit partial, of the handwritten tradition and on a global reconsideration of the editorial history work.